2017
DOI: 10.1186/s12911-017-0428-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an online pharmaceutical service using design science research

Abstract: Background: The rising prevalence of chronic diseases is pressing health systems to introduce reforms. Primary healthcare and multidisciplinary models have been suggested as approaches to deal with this challenge, with new roles for nurses and pharmacists being advocated. More recently, implementing healthcare based on information systems and technologies (e.g. eHealth) has been proposed as a way to improve health services. However, implementing online pharmaceutical services, including their adoption by pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 55 publications
0
28
0
8
Order By: Relevance
“…Other frameworks were used in 22% (11/50) of the studies, including the affordability, practicability, effectiveness, acceptability, side effects/safety and equity (APEASE) framework [ 52 ]; an extended De Lone and McLean information system success model [ 63 ]; Giddens structuration theory [ 51 ]; normalization process theory (NPT) [ 15 ]; organizational theory of implementation effectiveness [ 46 ]; reach, effectiveness, adoption, implementation, and maintenance framework [ 44 ]; technological frames (TF) [ 77 ]; the design science research methodology (DSRM) [ 85 ]; theory of change [ 48 ]; and TPB [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other frameworks were used in 22% (11/50) of the studies, including the affordability, practicability, effectiveness, acceptability, side effects/safety and equity (APEASE) framework [ 52 ]; an extended De Lone and McLean information system success model [ 63 ]; Giddens structuration theory [ 51 ]; normalization process theory (NPT) [ 15 ]; organizational theory of implementation effectiveness [ 46 ]; reach, effectiveness, adoption, implementation, and maintenance framework [ 44 ]; technological frames (TF) [ 77 ]; the design science research methodology (DSRM) [ 85 ]; theory of change [ 48 ]; and TPB [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…The personal characteristics of adopters were reported in more studies compared with social and cultural factors. Aspects such as self-efficacy (CFIR) were reported in 16 studies, highlighting the importance of the clinicians’ previous experiences, technical skills, knowledge, and abilities in general [ 36 , 39 , 42 , 53 , 58 , 59 , 64 , 70 , 85 ]. These factors are often linked to the users’ perceived ease of use [ 61 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmaceutical services in terms of pharmacist readiness to help are still lacking and the public will not get complete knowledge of herbal medicines. The results showed the role of pharmacists was limited due to lack of time, management, and skills in the use of information systems, 13 . This is supported by research which states that pharmacists are in pharmacies less than 20 hours/week, so that the interaction between pharmacists and patients is very low 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The Design Science Research Methodology [24] was applied in this study, which demonstrated its ability to study the connection between research and professional practices by designing, implementing and evaluating artifacts for a specific need. The process was inspired by Peffers' s three phases: problem identification, solution design, and evaluation [25].…”
Section: Methodsmentioning
confidence: 99%